2021
DOI: 10.25105/ijca.v3i2.10420
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Tax Avoidance, Sustainability Report Disclosure, and Earnings Management on Firm Value in the Digital Era With Corporate Governance as a Moderating Variables

Abstract: <p>This paper aims to determine whether tax avoidance, sustainability reporting, and earnings management affected firm value. Samples were collected from 80 companies listed on the Indonesian Stock Exchange (BEI)between 2015 and 2019. This research is an explanatory study that employs a quantitative approach and purposive sampling as the sampling technique, using the Absolute Difference Value Method to examine  the moderating variable’effect, and SPSS 23 to analyze the data. The finding indicate that whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…In the investigation of the effects of tax evasion, the publication of sustainability reports, and earnings management on firm value in the digital age. Andayani (2021) found that the relationship between digital transformation, sustainability, and purpose in multinational corporations, George and Schillebeeckx (2022) emphasize the need of coordinating digital activities with sustainable practices and organizational goals. In addition, the prospective effects of the Fourth Industrial Revolution and smart technologies are discussed in relation to digital entrepreneurship, taxes in the digital economy, and sustainable development in Africa by Mpofu (2023).…”
Section: Digital Taxation On Customs Efficiency and Sustainabilitymentioning
confidence: 99%
“…In the investigation of the effects of tax evasion, the publication of sustainability reports, and earnings management on firm value in the digital age. Andayani (2021) found that the relationship between digital transformation, sustainability, and purpose in multinational corporations, George and Schillebeeckx (2022) emphasize the need of coordinating digital activities with sustainable practices and organizational goals. In addition, the prospective effects of the Fourth Industrial Revolution and smart technologies are discussed in relation to digital entrepreneurship, taxes in the digital economy, and sustainable development in Africa by Mpofu (2023).…”
Section: Digital Taxation On Customs Efficiency and Sustainabilitymentioning
confidence: 99%
“…Other than that, one of the usefulness of e-Wallets that also attracts the consumer is the economic benefit. Since the system's initial launch e-Wallet companies have been " burning money" to carry out the marketing strategy by providing various kinds of discounts and promotions to their users to compete in this digital era (Pertiwi et al, 2021;Andayani, 2021). Therefore, users experience various benefits of the e-Wallet, and they will feel satisfied.…”
Section: Introductionmentioning
confidence: 99%